miR-330–5p in Small Extracellular Vesicles Derived From Plastrum testudinis-Preconditioned Bone Mesenchymal Stem Cells Attenuates Osteogenesis by Modulating Wnt/β-Catenin Signaling - Li, Xiaoyun; Cui, Yan; Lin, Qing; Wang, Panpan; Chen, Rumeng; Zhu, Xiaofeng; Yang, Li; Zhang, Ronghua (Frontiers in Molecular Biosciences, 2021)
The bone microenvironment is crucial for the growth and development of different types of osteocytes. Small extracellular vesicles (sEVs) secreted by bone mesenchymal stem cells are delivered to target cells where their contents regulate biological functions. Here, we evaluated the osteogenic effects and mechanism of sEVs derived from Plastrum Testudinis-preconditioned bone mesenchymal stem cells (PT-sEV). The osteogenic effects of PT-sEV were evaluated by the differentiation of osteoblasts and the alternation of bone quality and quantity in ovariectomized rats. The specific mechanism was explored by high-throughput sequencing and verified by transfection with the corresponding miRNA mimic and inhibitor. RNA-seq identified a unique enrichment of a set of miRNAs in PT-sEV compared with sEVs derived from untreated BMSCs. Overexpression or inhibition in vitro indicated that the osteogenic inducing potential of sEVs was mainly attributable to miR-330-5p, one of the most dramatically downregulated miRNAs in the PT-sEV fraction. Dual luciferase reporter assays showed that miR-330-5p negatively regulated osteogenesis by directly binding to the 3′ untranslated region of Tnc. Additional experiments showed that Tnc regulated Wnt/β-catenin signaling, and rescue experiment showed that miR-330-5p could restore β-catenin expression; additionally, animal experiments indicated that Wnt signaling was inactivated in the ovariectomized rats. These data demonstrated the regenerative potential of PT-sEV, which induced osteogenic differentiation of osteoblasts, leading to bone formation. This process is achieved by delivering miR-330-5p, which regulates Tnc to control Wnt/β-catenin signaling.